Applying Environmental Isotope Theory to Groundwater Recharge in the Jiaozuo Mining Area, China. (22nd May 2017) - Huang, Pinghua; Wang, Xinyi
Abstract : This study establishes the surface water evaporation line in theory and numerically simulates the δ D and δ 18 O value distribution interval of the recharge source of deep groundwater in the Jiaozuo mining area. The recharge elevation is calculated based on hydrogen and oxygen isotope tracer theory. Theoretical calculation and experimental data indicate that the surface water evaporation line in the study area in theory is almost the same as the measured surface data-fitting line. A significant linear relationship is identified between δ 18 O and the elevation of spring outcrop. The topography increases per 100 m, and the δ 18 O value reduces by 0.23‰ on average. The δ 18 O value is converted into formula to calculate the groundwater recharge elevation, which is approximately from 400 to 800 m. The measured tritium values of karst groundwater are greater than 3 TU. The second factor score is a fraction distribution in shallow groundwater and negative fraction distribution in spring and deep groundwater, which indicates that the Northern Taihang Mountain is the main recharge area, where carbonate-exposed areas exist. The research conclusion holds a certain value for the flood evaluation of local coal mines.